O ENDOMARKETING COMO INSTRUMENTO DE MOTIVAÇÃO E MELHORIA DA PRODUTIVIDADE EM EMPRESA DE SERVIÇO DE PEQUENO PORTE - Lino, Saulo Chagas (2009)
This dissertation approaches about the internal marketing as motivation and productivity improvement tool in small service company and it objectives investigate the relation between the internal marketing program implantation with the employees valorization, motivation and productivity based on literature and the case presented. It concluded that motivated and compromised employees with the company, it creates a partnership and confidence climate, developing, thus, an organizational culture inside work environment, generating life quality that generates productivity, and generates positive financial results, besides the customers fidelity, all that fortalice the company s image face to the other publics. It verifies the company Publicidade Comunicação Integrada Ltda. practices the internal marketing, with base on his actions related to the employees, with proposal to motivate the internal customers continually, searching their participation in the company s improvement process to integrate to the organizational culture; and it practices also the external communication, maintaining the customers fidelity.